Modernization of Physical Education of Students by Means of Choreography on the Basis of an Integrated Approach - Natalia Chuprun (Lesya Ukrainka Volyn National University, 2018)
To uncover the peculiarities of modernizing the physical education of students through the search for an effective technology of education and education by means of choreography on the basis of an integrated approach. The interest of scientists in solving the problem of integration of choreography in physical education has been revealed, but one should note the lack of scientific methodological developments in this direction. It is suggested to use choreography in the physical education of students on the basis of an integrated approach, which is aimed at motivational-value attitude to physical education and sports activities, orientation to physical perfection, mastering of the system of knowledge, skills and abilities from physical culture and choreography. The results of the research showed significant changes in the indicators of physical preparedness, physical health, theoretical preparedness, which occurred during the pedagogical experiment. It is proved that dance movement is an effective means of training the human body and can be effectively used in modern effective teaching and learning technologies that solve the problems of physical and intellectual development of students, meet the need for motor activity, and form a sustainable motivation to engage in physical education.